PENINGKATAN KETERAMPILAN HITUNG PENGURANGAN MELALUI PAPAN PENGURANGAN AJAIB (PANGAJI) DI KELAS 1B SD NEGERI PAKIS 1 SURABAYA - Utami, Wahyu Puspa Mawarni; Suliyastuti, Nunuk; Wirawati, Bekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the low calculation skills of reducing students in learning Indonesian at SD Negeri 1 Surabaya This research uses the Classroom Action Research method. “The purpose of this method is to improve reading comprehension and skills in students. The subjects in this study are students of class I B SD Negeri 1 Surabaya which amounted to 28 students, consisting of 13 women and 15 boys, The results of the research conducted at SD Negeri 1 Surabaya can be concluded that: Learning using the magic reduction board media (PANGAJI) can improve students' subtraction calculation skills. This can be shown in the results of the first cycle getting a percentage of 79% and increasing in the second cycle with a percentage of 96%”. Keywords: PANGAJI Media, Ability to Calculate Reduction, Elementary School.